(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
This article discusses the implementation of market economy reforms in the years of independence of the Republic of Uzbekistan, the peculiarities of the "Uzbek model", changes in the structure of the national economy during the period of market economy reforms and its development.